SPH-FEM simulation of shaped-charge jet penetration into double hull: A comparison study for steel and SPS. (1st November 2016) - Zhang, Zhifan; Wang, Longkan; Silberschmidt, Vadim V.; Wang, Shiping
Abstract: A high-speed metal jet capable to cause severe damage to a double-hull structure can be produced after detonation of a shaped charge. A Smoothed Particle Hydrodynamics (SPH) method with a mesh-free and Lagrange formulations has natural advantages in solving extremely dynamic problems. Hence, it was used to simulate the formation process of a shaped-charge jet. A Finite Element Method (FEM) is suitable for a structural analysis and is highly efficient for simulations of a complex impact process in a relatively short time; therefore, it was applied to develop a double-hull model. In this paper, a hybrid algorithm fully utilizing advantages of both SPH and FEM is proposed to simulate a metal-jet penetration into a double hull made of different materials – steel and SPS (Sandwich Plate System). First, a SPH-FEM model of a sphere impacting a plate was developed, and its results were compared with experimental data to validate the suggested algorithm. Second, numerical models of steel/SPS double-hull subjected to a shaped-charge jet were developed and their results for jet formation, a penetration process and a damage response were analysed and compared. The obtained results show that the velocity of the metal jet tended to decrease from its tip to the tail during its formation process. The jet broke into separate fragments after the first steel shell was penetrated, causing the damage zone of the second shell that grew as a result of continuous impact by fragments. As for the SPS structure, its damage zone was smaller, and the jet trended to bend becoming thinner due to the resistance of the composite layer. It was found that the polyurethane layer could have a protective effect for the second shell.